Cross-country comparisons of costs: the use of episode-specific transitive purchasing power parities with standardised cost categories - Schreyögg, Jonas; Tiemann, Oliver; Stargardt, Tom; Busse, Reinhard (Health economics, 2008)
International comparisons of healthcare costs are growing in importance for a number of different applications. The use of common approaches to converting costs such as GDP purchasing power parities (PPPs) often does not reflect price differences in healthcare in an appropriate manner. This means that new approaches need to be explored. The objective of this paper is to demonstrate the feasibility of using episode‐specific PPPs (ESPPPs) to facilitate cross‐country comparisons of healthcare costs and to compare this approach with other common approaches to conversion. Costs for five care episodes from hospitals in eight European countries were obtained from the EU HealthBASKET project. ESPPPs were created by using Fisher‐type PPPs in combination with the Eltetö–Köves–Szulc method at the episode level. Differences in ESPPPs among the five care episodes were discussed and compared with other common conversion approaches. We found that ESPPPs‐reflected prices and resource use more accurately than conventional conversion approaches such as GDP PPPs and medical care PPPs. This was particularly evident for labour‐intensive care episodes in which other conversion approaches revealed problems in the way that labour input had not been considered appropriately. The results demonstrate that ESPPPs are preferable to other common conversion approaches when international healthcare cost comparisons are performed. Copyright © 2008 John Wiley & Sons, Ltd.